2022
DOI: 10.3390/catal12090974
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Large Au Clusters and Even More Active Ag Nanoparticles Supported on Ceria-Zirconia: Impact of Particle Size and Potassium Ion Loading on Activity in Catalytic Transfer Hydrogenation

Abstract: Although heterogeneous monometallic gold catalysts are commonly more active when the gold particles are smaller, this study shows that the reverse is true in the case of liquid phase catalytic transfer hydrogenation of acetophenone with 2-pentanol. Higher catalytic activity of larger gold particles, i.e., over 30 nm in diameter, than of smaller particles of average 4 nm in size was observed. Moreover, this effect was contradictory to that observed for supported monometallic silver catalysts in which the intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
1
3
1
Order By: Relevance
“…They might be responsible for the fracture of these materials, but more studies are needed to confirm or disprove this hypothesis. The texture of the samples (Figure 5) is very similar to that of the previously published solid solutions prepared by us using a similar procedure, such as zirconium-doped ceria [43] and cerium-doped zirconia [44]. However, unlike for pure zirconia (Figure 5a) or zirconia doped with 5% Ce ions (Figure 5d), which fracture in large, irregular chunks using a mortar and pestle, both Zr 0.97 Mg 0.03 O x (Figure 5b) and Zr 0.95 Mg 0.05 O x (Figure 5c) show elongated structures with unusual fracture.…”
Section: Resultssupporting
confidence: 76%
“…They might be responsible for the fracture of these materials, but more studies are needed to confirm or disprove this hypothesis. The texture of the samples (Figure 5) is very similar to that of the previously published solid solutions prepared by us using a similar procedure, such as zirconium-doped ceria [43] and cerium-doped zirconia [44]. However, unlike for pure zirconia (Figure 5a) or zirconia doped with 5% Ce ions (Figure 5d), which fracture in large, irregular chunks using a mortar and pestle, both Zr 0.97 Mg 0.03 O x (Figure 5b) and Zr 0.95 Mg 0.05 O x (Figure 5c) show elongated structures with unusual fracture.…”
Section: Resultssupporting
confidence: 76%
“…The effect of surface enrichment in zirconium ions on the surface of the zirconium doped ceria support has been reported by us and other research groups earlier. 26 In the case of cerium-doped zirconia, an enrichment of the surface with cerium ions has been reported, though after a much higher thermal treatment than in the present study. 39 However, in this case, the low cerium content in the top 10 nm of the surface may be attributed to the presence of silver.…”
Section: Resultscontrasting
confidence: 55%
“…The zirconium-doped ceria and cerium-doped zirconia supports chosen for further testing were selected based on the results of our previous studies, which have shown that the Ce 0.85 Zr 0.15 O 2 and Zr 0.93 Ce 0.07 O 2 supports contain only one phase, the fluoritetype cubic ceria structure and tetragonal zirconia structure, respectively, and have the most beneficial properties. 25,26 As in the case of all of the silver catalysts for soot combustion in the literature cited in the Introduction section, the XRD studies have shown that the silver deposited onto Zr 0.93 Ce 0.07 O 2 is present in the metallic form (Fig. 1), even in the sample which The values of the specific surface area of the cerium-doped zirconia (ZC) and zirconium-doped ceria supports are 63 and 77 m 2 g −1 , respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations